1981
DOI: 10.1083/jcb.88.1.226
|View full text |Cite
|
Sign up to set email alerts
|

Myosin types and fiber types in cardiac muscle. I. Ventricular myocardium.

Abstract: Antisera against bovine atrial myosin were raised in rabbits, purified by affinity chromatography, and absorbed with insolubilized ventricular myosin. Specific anti-bovine atrial myosin (anti-bAm) antibodies reacted selectively with atrial myosin heavy chains, as determined by enzyme immunoassay combined with SDS-gel electrophoresis. In direct and indirect immunofluorescence assay, anti-bAm was found to stain all atrial muscle fibers and a minor proportion of ventricular muscle fibers in the right ventricle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(65 citation statements)
references
References 35 publications
4
61
0
Order By: Relevance
“…Heterogeneous accumulation of ␣-MHC protein has been reported in the adult heart of several mammalian species (Sartore et al, 1981;Litten et al, 1985) and electrophoretic analysis has revealed a higher V1 (␣-MHC homodimer)/V3 (␤-MHC homodimer) ratio in the right ventricular papillary muscles than in the left ventricular papillary muscles of the adult rat heart (Brooks et al, 1987). Our results show that a subset of sarcomeric genes is differentially expressed between left and right ventricular chambers during embryogenesis with probable functional repercussions for the developing heart.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous accumulation of ␣-MHC protein has been reported in the adult heart of several mammalian species (Sartore et al, 1981;Litten et al, 1985) and electrophoretic analysis has revealed a higher V1 (␣-MHC homodimer)/V3 (␤-MHC homodimer) ratio in the right ventricular papillary muscles than in the left ventricular papillary muscles of the adult rat heart (Brooks et al, 1987). Our results show that a subset of sarcomeric genes is differentially expressed between left and right ventricular chambers during embryogenesis with probable functional repercussions for the developing heart.…”
Section: Discussionmentioning
confidence: 99%
“…Two distinct cardiac myosin heavy chains, HCa and HC#, are recognized to exist in the mammalian heart, and are comprised of V1 and V3 as homodimers of HCa and HC#, respectively, and V2 as a heterodimer (1). Enzymatic (2, 3, 4), electrophoretic (5), and immunochemical (6,7,8) analyses have revealed (a) that the predominant form ofventricular isomyosin varies according to the species examined, (b) that HCa is the predominant isoform in the atrium, whereas HCj# is predominant in the ventricles of larger animals including humans, and (c) that the relative proportions ofthese isozymes can be changed by aging, hormonal state, and pressure overload in laboratory animals.…”
Section: Introductionmentioning
confidence: 99%
“…By immunohistochemical methods, Sartore et al (10) showed myosin polymorphism in Purkinje fibers of chicken atrium, and variable reactivity of Purkinje fibers with anti-bovine atrial myosin antibody in the bovine ventricle (8), but the presence and distribution ofmyosin isozymes in the whole conduction system has not been elucidated, especially in humans. By using monoclonal antibodies, we have now demonstrated the detailed distribution of myosin isozymes in normal human myocardium including the conduction system.…”
mentioning
confidence: 99%